Synthesis and Growth Mechanism of Ni Nanotubes and Nanowires - Wang Yiqian; Li Xiaoru; Song Guojun; Peng Zhi; Yu Yongming; She Xilin; Li Jianjiang (Nanoscale Research Letters, 2009)
Abstract Highly ordered Ni nanotube and nanowire arrays were fabricated via electrodeposition. The Ni microstructures and the process of the formation were investigated using conventional and high-resolution transmission electron microscope. Herein, we demonstrated the systematic fabrication of Ni nanotube and nanowire arrays and proposed an original growth mechanism. With the different deposition time, nanotubes or nanowires can be obtained. Tubular nanostructures can be obtained at short time, while nanowires take longer time to form. This formation mechanism is applicable to design and synthesize other metal nanostructures and even compound nanostuctures via template-based electrodeposition.